Corneal Neurotization With a Great Auricular Nerve Graft: Effective Reinnervation Demonstrated by In Vivo Confocal Microscopy. Issue 5 (May 2018) - Benkhatar, Hakim; Levy, Ora; Goemaere, Isabelle; Borderie, Vincent; Laroche, Laurent; Bouheraoua, Nacim
Abstract : Purpose: We describe the first case of minimally invasive corneal neurotization with the great auricular nerve (GAN) to treat unilateral neurotrophic keratopathy. We assessed corneal sensation and reinnervation by esthesiometry and confocal microscopy over 12 months of follow-up, and we provide a detailed description of the surgical technique. Methods: Corneal neurotization was successfully achieved with the ipsilateral GAN in a 58-year-old woman. Cochet–Bonnet esthesiometry and in vivo confocal microscopy were performed before and after corneal neurotization, to monitor the recovery of corneal sensation and corneal reinnervation by subbasal nerve fibers. Results: Neurotrophic keratopathy was a complication of the surgical treatment of meningioma. Before surgery, the patient had no corneal sensation or corneal innervation. Six months after surgery, confocal microscopy confirmed regrowth of a large number of nerve fibers in the subepithelial space of the cornea. Nine months after surgery, a central esthesiometry score of 10-mm was attained. Conclusions: Corneal neurotization leads to reinnervation of the cornea and recovery of ocular sensation in adults. The GAN is suitable for use in corneal neurotization because of its anatomical proximity and the low level of associated morbidity. Confocal microscopy demonstrated the occurrence of corneal reinnervation, which preceded the recovery of corneal sensation.